(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this article, when examining the antioxidant activity of a mixture of Japanese safflower (lat. Styphnolobium japo’nicum) and Lupin (lat. Lupus) plants found in Uzbekistan, high antioxidant activity was detected in a 1:1 ratio, so we created a biological food supplement for the treatment of diabetes from this 1:1 ratio and named it “As Lupinus”. In order to analyze the biological activity of the “As Lupinus” food supplement, the effect of the “As Lupinus” food supplement on the amount of glucose and insulin in rat blood plasma in alloxan diabetes was studied at the Tashkent Institute of Bioorganic Chemistry using the in vivo method. The aim of the study was to conduct preclinical testing of the biological activity of this “As Lupinus” food supplement and to create and apply it in practice.